2021
DOI: 10.3389/fgene.2021.664814
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of Allelic Variation Underlying Floral and Fruit Traits in Flare Tree Peony (Paeonia rockii) Using Association Mapping

Abstract: Allelic variation in floral quantitative traits, including the elements of flowers and fruits, is caused by extremely complex regulatory processes. In the genetic improvement of flare tree peony (Paeonia rockii), a unique ornamental and edible oil woody species in the genus Paeonia, a better understanding of the genetic composition of these complex traits related to flowers and fruits is needed. Therefore, we investigated the genetic diversity and population structure of 160 P. rockii accessions and conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 89 publications
(127 reference statements)
0
3
0
Order By: Relevance
“…Because the phenotype is the result of the interaction of genotype and external environment and the diversity of phenotypic traits is the manifestation of genotype difference in morphology, the phenotypic variation in the population mainly depends on the genotype difference when all accessions used in this study were grown in the same condition. In FTP, Pang et al [59] reported phenotypic variation coefficients ranging from 10% to 30% based on 32 traits of 150 accessions, but Wu et al [60], on the diversity of 29 quantitative traits of 462 accessions, found that the coefficient of genetic variation was 9.52-112.1%. By the genetic diversity of 28 quantitative traits of 180 accessions, this study revealed a genetic variation coefficient of 12.33-108.73%, which was similar to Wu et al [60].…”
Section: Diversity Of Phenotypic Traitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the phenotype is the result of the interaction of genotype and external environment and the diversity of phenotypic traits is the manifestation of genotype difference in morphology, the phenotypic variation in the population mainly depends on the genotype difference when all accessions used in this study were grown in the same condition. In FTP, Pang et al [59] reported phenotypic variation coefficients ranging from 10% to 30% based on 32 traits of 150 accessions, but Wu et al [60], on the diversity of 29 quantitative traits of 462 accessions, found that the coefficient of genetic variation was 9.52-112.1%. By the genetic diversity of 28 quantitative traits of 180 accessions, this study revealed a genetic variation coefficient of 12.33-108.73%, which was similar to Wu et al [60].…”
Section: Diversity Of Phenotypic Traitsmentioning
confidence: 99%
“…In FTP, Pang et al [59] reported phenotypic variation coefficients ranging from 10% to 30% based on 32 traits of 150 accessions, but Wu et al [60], on the diversity of 29 quantitative traits of 462 accessions, found that the coefficient of genetic variation was 9.52-112.1%. By the genetic diversity of 28 quantitative traits of 180 accessions, this study revealed a genetic variation coefficient of 12.33-108.73%, which was similar to Wu et al [60]. As the plants used both by Wu al.…”
Section: Diversity Of Phenotypic Traitsmentioning
confidence: 99%
See 1 more Smart Citation